Body Mass and Femur Length Are Inversely Related to Repetitions Performed in the Back Squat in Well-Trained Lifters. Issue 3 (March 2019) - Cooke, Daniel M.; Haischer, Michael H.; Carzoli, Joseph P.; Bazyler, Caleb D.; Johnson, Trevor K.; Varieur, Robert; Zoeller, Robert F.; Whitehurst, Michael; Zourdos, Michael C.
Abstract : Abstract: Cooke, DM, Haischer, MH, Carzoli, JP, Bazyler, CD, Johnson, TK, Varieur, R, Zoeller, RF, Whitehurst, M, and Zourdos, MC. Body mass and femur length are inversely related to repetitions performed in the back squat in well-trained lifters. J Strength Cond Res 33(3): 890–895, 2019—The purpose of this research note was to examine whether relationships existed between anthropometrics (body mass, body fat percentage [BF%], and femur length) and descriptive characteristics (age and sex) with repetitions performed to failure at 70% of 1 repetition maximum (1RM) in the back squat. Fifty-eight subjects (males = 43, females = 15; age: 23 ± 3 years, training age: 5.5 ± 2.5 years, body mass: 80.65 ± 16.34 kg, BF%: 10.98 ± 3.53%, and femur length: 47.1 ± 2.6 cm) completed a 1RM squat followed by one set to failure at 70% of 1RM. Total repetitions performed at 70% of 1RM were 14 ± 4 (range: 6–26). Bivariate correlations showed significant inverse relationships between body mass ( r = −0.352, p = 0.003), BF% ( r = −0.278, p = 0.014), and femur length ( r = −0.265, p = 0.019), with repetitions performed. No significant relationships existed between age and sex ( p > 0.05), with repetitions performed. All these variables entered into a standard multivariate regression. The model R 2 was 0.200, and body mass had the largest influence ( p = 0.057) because relative importance analysis demonstrated body mass to contribute to 43.87% of the variance (of the R 2 ) in repetitions performed. No other variable was significant or approached significance ( p > 0.05). Our results reveal that body mass, BF%, and femur length all are inversely related to repetitions performed at 70% of 1RM in the back squat.